Between contentment and prosperity: A study of 1 Timothy 6:3–12 in light of the prosperity teaching in Nigeria - Ademiluka, Solomon O. (In die Skriflig/In Luce Verbi, 2022)
The prosperity theology is the teaching that every person is purposed by God to be prosperous in all areas of life with emphasis on financial abundance. Since the early 1980s, the gospel of prosperity has been firmly established in Nigeria. This article examined this theology considering the demand on Christians for godliness with contentment in 1 Timothy 6:3–12. It employed the descriptive approach and the historical-critical exegesis. This study found that the prosperity preachers often support their claims with the Bible, but texts are usually cited without regard to their literary or historical contexts. It also discovered that 1 Timothy 6:3–12 does not teach that Christians should not be rich, but condemns inordinate desire for money because of the evils associated with it. The text supports benevolence from the wealthy towards the needy, but does not make giving mandatory. This article concluded that the prosperity gospel is at variance with the teaching on godliness with contentment. Instead, it encourages greed for money among Christians, particularly in view of the claim that poverty is proof of unrighteousness. The doctrine of giving in order to receive from God contradicts the principle of giving as found in 1 Timothy 6 and other relevant New Testament texts. Contribution: The article is a contribution to Christian ethics with a special focus on Christian attitude to money. It postulates that the prosperity teaching that all must be rich, contradicts the demand on Christians for godliness with contentment.
free